2022
DOI: 10.1186/s12870-022-03845-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of effector CEP112 that promotes the infection of necrotrophic Alternaria solani

Abstract: Background Alternaria solani is a typical necrotrophic pathogen that can cause severe early blight on Solanaceae crops and cause ring disease on plant leaves. Phytopathogens produce secretory effectors that regulate the host immune response and promote pathogenic infection. Effector proteins, as specialized secretions of host-infecting pathogens, play important roles in disrupting host defense systems. At present, the role of the effector secreted by A. solani during infection remains unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…A transcriptome analysis of the genes in potato and A. solani that exhibited interactions in the early infection stage showed that cell wall-degrading enzymes and metabolic processes may be important for early A. solani infection of potato [ 14 ]. In our previous study, we reported that the effector proteins AsCEP112, AsCEP19 and AsCEP20, and play important roles in late-stage A. solani infection of potato leaves [ 15 , 16 ]. In the current study, we inoculated potato leaves with A. solani and found that near the inoculation site, there were obvious whorl symptoms and tissue collapse within 72 h, and the disease spread rapidly between 96 and 120 h. Therefore, we focused on protein interaction in the late stage of infection, which was further investigated by genome-wide transcriptomic analyses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A transcriptome analysis of the genes in potato and A. solani that exhibited interactions in the early infection stage showed that cell wall-degrading enzymes and metabolic processes may be important for early A. solani infection of potato [ 14 ]. In our previous study, we reported that the effector proteins AsCEP112, AsCEP19 and AsCEP20, and play important roles in late-stage A. solani infection of potato leaves [ 15 , 16 ]. In the current study, we inoculated potato leaves with A. solani and found that near the inoculation site, there were obvious whorl symptoms and tissue collapse within 72 h, and the disease spread rapidly between 96 and 120 h. Therefore, we focused on protein interaction in the late stage of infection, which was further investigated by genome-wide transcriptomic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…After 7 days of incubation at 25 °C in the dark, the active mycelia growing on the T4 plate were removed with sterile slide, and the T4 plate was irradiated with UV light (ultraviolet lamp power of 8 W) for 10 min. Finally, the T4 plate was cultured in the dark for alternating periods of 25 °C/12 h and 20 °C/12 h for 3 days [ 15 ]. When the T4 plate was covered with black spores, 2 ml sterile distilled water was added to wash the T4 plate, and the spores were collected, centrifuged at 10,000 rpm, and then diluted with sterile water to obtain a 10 6 spores/mL suspension.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Abolition of JA/ET pathways in the presence of PAMPs may be sufficient to derepress leaf senescence and therefore promote pathogen virulence. Previous studies have shown that an A. solani isolate of EBDC secretes a proteinaceous effector that increases virulence in tomato, and induces expression of senescence genes in Nicotiana benthamiana , primarily SEN4, SAG12 , and DHAR1 [114]. Orthologs of these genes are not DEGs.…”
Section: Discussionmentioning
confidence: 99%